Analisis efektivitas biosekuriti biocheck.UGent dan Layer Farm Assessment Tools (LFAT) terhadap kelayakan usaha peternakan ayam petelur - Luqyana Barda; Bambang Sektiari Lukiswanto; Anwar Ma’ruf; Mufasirin; Yuliana Puspitasari4; Eduardus Bimo Aksono (Agrivet : Jurnal Ilmu-Ilmu Pertanian dan Peternakan (Journal of Agricultural Sciences and Veteriner), 2026)
Biosecurity is essential for disease prevention and economic sustainability in layer farming. This study analyzed the implementation of biosecurity and its relationship with economic feasibility in medium-scale layer farms in East Lombok Regency, while comparing the effectiveness of Biocheck.UGent and Layer Farm Assessment Tools (LFAT). An observational cross-sectional study was conducted on ten medium-scale farms (1,500–5,000 birds) selected purposively. Biosecurity was assessed using Biocheck.UGent and LFAT, while economic feasibility was evaluated through Break Even Point (BEP), Payback Period (PP), and Benefit Cost Ratio (B/C Ratio). Data were analyzed using Independent Sample t-tests, Pearson correlation analysis, and effect size (Cohen’s d) at a 5% significance level. The results showed that internal biosecurity, biosecurity practices, and farm management had a significant effect on BEP and PP. . The results indicated that internal biosecurity had the strongest and significant correlation with BEP and PP, highlighting its dominant role in operational efficiency. In contrast, no biosecurity component was significantly correlated with the B/C Ratio. Biocheck.UGent proved more effective in assessing technical biosecurity impacts, whereas LFAT better captured managerial aspects of farming systems.